(untitled) (Globalization and Business, 2023)
Offering of new ecologically clean thermodynamic build- ings (thermos) for the fresh start-up wine producers is highly relevant in the development of wine quality and wine tourism. Hereby we are presenting alternatives, traditional and modern technologies and building materials that can be applied in wine tourism these are the houses made of renew- able non-traditional materials (nails, clay). They are compared with materials that are used in the construction of tourist in- frastructures today. We have studied ecologically clean, harmless, cheap, energy efficient, economically efficient products - taking into consideration their sustainability, comfort, physical data and energy efficiency. Eco-homes,which can be used in wine tourism, are also attractive due to the fact that the thermal physiological data of renewable materials used in eco-shops (reduction of energy losses) make daily costs cheaper. Construction of such ecosystems will help the creation of a road network for camps and mortar network in Georgia, where wine tasting would be possible. Also, by using the panels, it would be possible to arrange a simple type of portable tents and bungalows according to seasons. All this will im- prove servicing in wine tourism. In the regions rich in wine traditions and vine culture, such as Kakheti – it is important to focus on the healing prop- erties of Georgian wines in the process of wine tourism de- velopment, wines which will be made in the ecologically safe environment that will help attracting more tourists, develop- ment of Georgian winemaking and viticulture and stimulation of internal tourism as well as creation of jobs in the region, popularization of healing tourism and touristic image of the country.